2018
DOI: 10.1080/01634372.2018.1475438
|View full text |Cite
|
Sign up to set email alerts
|

“I’m just trying to cope for both of us”: Challenges and supports of family caregivers in participant-directed programs

Abstract: Recently, national attention has focused on the needs of family caregivers providing complex chronic care, noting the necessity to better understand the scope of challenges they encounter. Although a robust body of literature exists about the scope of family caregiving, little is known specifically about the experiences and perspectives of family caregivers who support participant directed (PD) participants, particularly across the caregiving trajectory. Therefore, the aim of this qualitative descriptive study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…17 Improved caregiver satisfaction and emotional well-being have been reported in other participant-directed programs. 16,18…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…17 Improved caregiver satisfaction and emotional well-being have been reported in other participant-directed programs. 16,18…”
mentioning
confidence: 99%
“…8,15 Family caregivers value the choice and flexibility afforded by participant-directed programs. 16 They report reduced stress associated with using paid caregivers through VDC, because of the control they have over hiring decisions and the ability to work with a consistent and reliable paid caregiver over an extended timeframe. 17 Family caregivers in VDC value scheduling caregiving help when it is needed, rather than according to an agency's schedule.…”
mentioning
confidence: 99%
“…Studies indicated that caregiving support have a significant role for primary caregivers of children with LD [23]. School and educational workload make it difficult for caregivers to find enough time to meet their basic needs (e.g., visiting a doctor), which in turn associated with caregivers' feelings of burnout [52,62,63]. For example, full-time working parents experiencing a range of home-, work-and child-related difficulties have reported more concerns about their physical and psychological health and less interest in social activities [52].…”
Section: Caregiving Supportmentioning
confidence: 99%
“…Since mothers are usually the primary caregiver in all over the world [64], mothers who are not receiving adequate caregiving support can be regarded as a risky group in terms of psychological and physical health. Social policies providing services for fulfilling mothers' physical and social needs can also support their participation in social life [63]. Researchers should elaborate on what kind of resources mothers of children with LD need or use in case of a lack of caregiving support in future studies.…”
Section: Caregiving Supportmentioning
confidence: 99%
“…Another widely addressed caregiving domain is the support in organizational matters, which is very important since caregivers often nd it di cult to interact with the health care system [27]. However, such apps contained mainly calendar, reminder, or documentation features and rarely addressed issues with caregiving arrangements and related bureaucracy.…”
Section: Caregiving Domainsmentioning
confidence: 99%